Conseiller, expert et consultant en patrimoine : la construction d’une figure de l’Éthiopie contemporaine - Guillaume Blanc; Marie Bridonneau (EchoGéo)
Since their inclusion in the World Heritage List in 1978, the small town of Lalibela and the Semèn mountains are moving in step with the transformation of the contemporaneous Ethiopian State and the reinforcement of the globalization of heritage led by, among others, an elite of “consultants”. Articulator of scales manipulating or manipulated by public authorities, the consultant contributes at the same time to anchor the local spaces in the inconsistency of the so-called international norms, to open the country to the neoliberal globalization and to strengthen the power of the mängist. Through the history and the geography of Semèn and Lalibela, this article sketches the portrait of this key figure of the Glocal Ethiopia.